Evaluasi Kinerja Tenaga Pendidik dan Kependidikan dalam Upaya Meningkatkan Mutu Pendidikan di MAN 1 Ponorogo - Siti Nurul Istiqomah; Fata Asyrofi Yahya; Arina Haq (Southeast Asian Journal of Islamic Education Management, 2025)
This research is motivated by an academic problem in the form of a weak performance evaluation system in educational institutions. The issue of performance evaluation that is not maximized affects the quality of education. The preliminary research results in the field found that educators and education personnel perform at MAN 1 Ponorogo. The objectives of this study include three things, namely, describing and analyzing the process of evaluating the performance of educators and education personnel, evaluating the performance techniques of educators and education personnel, and the success of evaluating the performance of educators and education personnel in improving the quality of education. This research uses a qualitative approach with a case study type. Data collection was carried out using interviews, observation, and documentation techniques. The data analysis technique successively starts from data condensation, presentation, and conclusion drawing. Data were tested for validity through triangulation of techniques, sources, and length of time. The results of this study include: first, the performance evaluation process includes setting specific evaluation roles and objectives, dividing tasks to related human resources, checking and monitoring the performance of educators and education personnel, checking and monitoring the performance of educators and education personnel, assessing the performance of educators and education personnel, and finally conveying the results of performance evaluation assessments. Second, performance evaluation techniques include direct techniques in carrying out supervision actions to educators and indirect techniques in assessing Employee Performance Targets (SKP) to educators and education personnel. Third, the success of improving the quality of education is marked by the achievement of quality improvement indicators used. The results of this study indicate that performance evaluation that is carried out optimally is in line with improving the quality of education